PENGARUH METODE ROLE PLAYING TERHADAP HASIL BELAJAR IPS SISWA KELAS V PONTIANAK BARAT - Wanti Dewi Kardiaanti; Suhardi Marli; Endang Uliyanti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThe purpose of this research  was to analyze the influence of the Role Playing learning method on the learning outcomes of Social Sciences of fifth grade students of West Pontianak 54th Elementary School. The research method used was an experiment, a form of Quasi Experimental type of non equivalent group design. The research population was all fifth grade students of West Pontianak Elementary School 54 with the number of students were 71 students. The sampling technique uses purposive sampling. The technique used is direct observation and measurement. Data collection tools in the form of observation sheets and multiple choice tests. The results of data analysis are, the average score of the control class post-test is 61.03 and the experiment is 66.56. Based on the results of the t-test calculation obtained by tcount 2.95> ttable 1.98, then Ha is accepted. This shows that there are differences in the learning outcomes of the control class students with the experimental class. Calculation of effect size is 0.74 with medium criteria. The conclusion of this researchis that there is the influence of the Role Playing learning method on the learning outcomes of Social Sciences in fifth grade students of West Pontianak 54 Elementary School in the medium category. Keywords: Learning Methods for Role Playing, Learning Outcomes, Social Sciences